2020
DOI: 10.1029/2020gh000299
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Exposure in Ann Township, Myanmar, as a Function of Land Cover and Land Use: Combining Satellite Earth Observations and Field Surveys

Abstract: Despite progress toward malaria elimination in the Greater Mekong Subregion, challenges remain owing to the emergence of drug resistance and the persistence of focal transmission reservoirs. Malaria transmission foci in Myanmar are heterogeneous and complex, and many remaining infections are clinically silent, rendering them invisible to routine monitoring. The goal of this research is to define criteria for easy-to-implement methodologies, not reliant on routine monitoring, that can increase the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…The regression analyses in this study support previous work showing that in this region, targeting certain groups based on older age, male gender, high-risk occupation, and frequent engagement in other outdoor activities, like collecting water and time spent in the forest, may improve the effectiveness of these screen-and-treat strategies. The high heterogeneity seen in prevalence of subclinical malaria even in adjacent villages is consistent with previous research, 14 and suggests that elimination efforts should target specific foci within geographical units such as at the township level.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The regression analyses in this study support previous work showing that in this region, targeting certain groups based on older age, male gender, high-risk occupation, and frequent engagement in other outdoor activities, like collecting water and time spent in the forest, may improve the effectiveness of these screen-and-treat strategies. The high heterogeneity seen in prevalence of subclinical malaria even in adjacent villages is consistent with previous research, 14 and suggests that elimination efforts should target specific foci within geographical units such as at the township level.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies from the region have identified risk factors for subclinical malaria infection, including age (young adults) and male gender, 6 , 13 as well as occupations that involve outdoor exposure, such as farming and logging. 13 , 14 In preparation for a larger cohort study aiming to measure the transmission potential of subclinical malaria, we evaluated the dynamics of subclinical malaria over a period of 6–12 weeks, using weekly or biweekly follow-up, respectively, at three epidemiologically distinct sites in Myanmar. The aims were to determine whether low-density, subclinical malaria infections persisted over time and could be reliably detected using usPCR with successive testing, and whether certain demographic characteristics are associated with the prevalence and persistence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has established some linkages between the LCLU types and malaria risks. Specifically, deforestation and agricultural development have been shown to influence mosquito species abundance and malaria incidence through changes to the ecology of vector species as well as the nature and stage of the agricultural development determining patterns of human contact with vectors [ 7 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to capturing and highlighting the areas where malaria exposure and transmission are more likely, LCLU maps could also be of great importance for malaria treatment efforts because they could provide information about the distribution of human settlements at large spatial scales. This is especially crucial for rural villages with low economic well-being and limited access to care [ 16 , 17 ]. However, creating LCLU maps that offer meaningful information about village distribution across the country is challenging because (1) it requires the mapping to be implemented at a 30-meter or higher resolution to ensure the successful mapping of remote villages (according to our personal observations, many remote villages in Myanmar are fairly small in extent and consist of a few buildings with small footprints), which are known to serve as the remnant pools of malaria [ 18 ], and (2) villages are quite similar to many bare ground features (e.g., riverbanks, bare mountain tops) in terms of their spectral signature.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion and elevation of community priorities is a key principle of the field of Environmental Justice. As has been shown in many scientific and research contexts, the inclusion of historically marginalized communities in geoscience research results in higher quality research and broad, critical, and timely societal impacts (Ballard & Huntsinger, 2006; Bonney et al., 2009; Dalbotten et al., 2017; Danielsen et al., 2014; Harris et al., 2021; Hoffman‐Hall et al., 2020; Moysey, 2011; Pierotti & Wildcat, 2000; Price & Lee, 2013; Ramirez‐Andreotta et al., 2014, 2016; Shirk et al., 2012; Smythe et al., 2010; Southern et al., 2022).…”
Section: Introductionmentioning
confidence: 99%